2015
DOI: 10.1590/s1413-70542015000400005
|View full text |Cite
|
Sign up to set email alerts
|

THERMAL STABILITY OF Pinus oocarpa AND MAIZE COB PARTICLEBOARDS

Abstract: Agricultural waste materials are generated in large quantities in Brazil. These can accumulate and cause serious environmental problems. One of the most commonly generated wastes in the brazilian agricultural culture is the maize cob. Being lignocellulosic in nature, the maize cob can find use as the raw material in the production of particleboards mainly concerned with furniture making. Therefore, studies regarding its thermal stability and fire resistance would be interesting. The aim of this study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…The literature has reported several attempts to produce more sustainable panels. These alternatives involve the use of natural adhesives (Goulart et al, 2012;Carvalho et al, 2014), low formaldehyde release (Roffael & Behn, 2012) and alternative raw material, derived from lignocellulosic wastes such as sugarcane bagasse (Mendes et al, 2012), rice husk (Melo et al, 2009;César et al, 2017), maize cob (Scatolino et al, 2013(Scatolino et al, , 2015Sekaluvu et al, 2014), coffee husk (Mendes et al, 2010), peanut husk (Guler & Buyuksari, 2011), corn straw (Silva et al, 2015), vine (Vitis vinifera L.) (Yeniocak et al, 2014), castor husk (Silva et al, 2016) and rapeseed straw (Dukarska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has reported several attempts to produce more sustainable panels. These alternatives involve the use of natural adhesives (Goulart et al, 2012;Carvalho et al, 2014), low formaldehyde release (Roffael & Behn, 2012) and alternative raw material, derived from lignocellulosic wastes such as sugarcane bagasse (Mendes et al, 2012), rice husk (Melo et al, 2009;César et al, 2017), maize cob (Scatolino et al, 2013(Scatolino et al, , 2015Sekaluvu et al, 2014), coffee husk (Mendes et al, 2010), peanut husk (Guler & Buyuksari, 2011), corn straw (Silva et al, 2015), vine (Vitis vinifera L.) (Yeniocak et al, 2014), castor husk (Silva et al, 2016) and rapeseed straw (Dukarska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies in literature have shown the mixture of agricultural wastes with wood species such as coffee husks in association to Eucalyptus urophylla (Mendes et al, 2010); castor husk and Pinus oocarpa (Silva et al, 2016) and maize cob to pine wood (Scatolino et al, 2015). All studies evaluated the influence of different proportions of lignocellulosic waste on the physical and mechanical properties of particleboards.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura relata vários estudos com a utilização de resíduos agrícolas ou industriais na produção de painéis aglomerados como bagaço de cana (MENDES et al, 2012), casca de arroz (MELO et al, 2009), sabugo de milho (SCATOLINO et al, 2015;SEKALUVU et al, 2014), casca de café (MENDES et al, 2010), casca de amendoim (GULER; BUYUKSARI, 2011), palha de milho (SILVA et al, 2015), podas de videira (Vitis vinifera L.) (YENIOCAK et al, 2014) e casca de mamona (SILVA et al, 2016).…”
Section: Introductionunclassified
“…Different researchers have reported the utilization of agricultural wastes in particleboards production, such as sugarcane bagasse (Mendes et al, 2012), rice husk (Melo et al, 2009), maize cob (Scatolino et al, 2013;Scatolino et al, 2015;Sekaluvu;Tumutegyereize;Kiggundu, 2014), coffee husk (Mendes et al, 2010), peanut husk (Guler; Buyuksari 2011), corn straw (Silva et al, 2015), vine (Vitis vinifera L.) (Yeniocak et al, 2014) and castor husk (Silva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%